Mikania mellosilvae sp. nov. (Asteraceae: Eupatorieae) from the Atlantic Forest of Brazil and lectotypification of Mikania candolleana. (2nd December 2021) - Antar, Guilherme Medeiros; Oliveira, Caetano Troncoso; Pirani, José Rubens
Abstract : A new species, Mikania mellosilvae, from Bahia and Minas Gerais States, is described and illustrated. Until now, herbarium material of this species has been misidentified, as well as in articles referring to the collections, as Mikania candolleana Gardner. The similarities and differences between the two taxa are discussed. Although both species share a lianescent habit, similar leaf shape and inflorescence structure, they differ mainly in the leaf base form, stem indumentum, peduncle and flower measurements and by their geographical distribution, as M. mellosilvae is endemic to the Atlantic Forest domain and M. candolleana is endemic to the Cerrado domain, both in eastern Brazil. We also provide a distribution map for both species, a lectotypification for the name M. candolleana, as well as a detailed description of the new taxon, along with illustrations including habitat pictures, a preliminary conservation assessment and comments on its ecology.